Design of honeysuckle harvesting robot based on MBSE and TRIZ. Issue 1 (1st February 2023) - Liu, Wenyue; Du, Xinyue; Fu, Mengyu; Gao, Guohua
Abstract: The design of field operation robots is a complex and comprehensive task. The external environment that changes at any time imposes strict requirements on the design. In this paper, we propose a systematic and innovative design of a honeysuckle harvesting robot using MBSE and TRIZ methods, deeply excavating the potential failure factors in 5M1E and effectively completing the robot design task through requirements analysis, functional modeling, and architecture design to ensure the integrity and comprehensiveness of the process.